Interpolating sequences Hp with p < 1 - Kabaila, V. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Кабайла. Интерполяционные последовательности для классов Нр в случае р < 1V. Kabaila. Hp klasės interpoliacinės sekos p < 1 atveju